Agendas, Horizons, and the Canadian Introductory Reader: A Review Essay - Ilya Parkins (Atlantis)
Abstract This essay reviews three Canadian Introduction to Gender and Women’s Studies readers, asking what they might reveal about the investments and values that animate teaching in Gender and Women’s Studies. It argues that the texts are incommensurable with current theoretical and methodological trends in Gender and Women’s Studies and considers what each offers to the field.